The Effect Of Loss Aversion, Confirmation Bias, And Herd Behavior In Online Loan Decision-Making Among Economics Students In Palembang City - Asma Mario; Angka Wijaya; Pandriadi Pandriadi; Dhea Rizky Amelia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study was motivated by concerns about the prevalence of online loan (Pinjol) problems that ensnare students, even leading to stress and suicide. This phenomenon highlights the importance of understanding the factors that influence students' decisions to use Pinjol services. Based on previous research findings, there are three relevant aspects of behavioral economics, namely loss aversion, confirmation bias, and herd behavior. This study uses a quantitative approach with the Ordinary Least Square (OLS) multiple linear regression analysis method using EViews 13 software. The results show that the three independent variables, namely loss aversion, confirmation bias, and herd behavior, have a proven effect on students' decisions to take out online loans. These findings confirm that students' economic behavior in the context of online loans is not only influenced by rational factors, but also by psychological and social biases. The implications of this study are expected to form the basis for prevention efforts and financial literacy education so that students can be wiser in managing their financial needs and avoid the trap of online loans.